(untitled) (Damak Campus Journal, 2025)
The Garudamahapurana, one of the eighteen Mahāpurāṇas, encompasses a variety of rituals and mythological stories. Within this, The Preta Kalpa addresses death, the journey of the soul after death, and the rituals intended to ensure a peaceful passage for the departed soul. Investigating the death rituals outlined in this text reveals their integral role in preserving cultural traditions, offering insight into how ancient Hindu society understood death and the afterlife. These rituals are seen as essential for maintaining both social and cosmic harmony. According to Hindu philosophy, the soul -Atman- is eternal, and the rituals in The Preta Kalpa are crucial in facilitating the soul’s journey in the cycle of reincarnation or its attainment of liberation moksha. The importance of these rituals lies in their ability to support the soul’s transition between realms, reflecting a profound grasp of the metaphysical concepts of life, death, and rebirth. Additionally, death rituals serve a sociological function by organizing community life and reinforcing societal norms. Research has explored how the rituals prescribed in The Preta Kalpa promotes social cohesion by ensuring that the deceased’s soul is honored in accordance with their social standing and other roles within society. The research aims to explore The Garudamahapurana and analyze the implications of gender dynamics within the socio-cultural framework of Hindu death rituals with the theorists like Judith Butler, Raewyn Connell, Candace West & Don Zimmerman, and Kimberlé Crenshaw. The required stanzas from The Preta Kalpa of The Garudamahapurana have derived as the source of primary data and the other referential articles from differentjournals have been used as the secondary data to analyze and in exploring death rituals described within The Preta Kalpa in The Garudamahapurana. As for the exploring gender dynamics, in The Garudamahapurana, gender shapes who does which death rituals. Men—especially the eldest son—are expected to perform the main rites, like lighting the funeral pyre and helping the soul continue its journey. Women usually take supporting roles, such as preparing offerings or mourning at home, and they are often not allowed to do the central rituals. These practices come from old ideas about duty and purity. Today, however, many families adjust these customs, and women sometimes take a bigger part, showing that gender roles are changing.